To the anniversary of Krasovitov plastic surgery with detached skin flaps – from creating a method to current relevance - S. B. Bogdanov; V. A. Aladina; S. N. Kurinniy; A. V. Polyakov; A. N. Blazhenko; M. L. Mukhanov (Инновационная медицина Кубани)
The article describes the life path of a famous Kuban surgeon Vkadimir K. Krasovitov. The historical aspects of the creation of full-layer skin plasty technique according to Krasovitov are presented, the relevance of its use in our days is analyzed, and the development of new types of skin autoplastics is presented. In addition, the author describes the history of candidate dissertation of V.K. Krasovitov's, as well as the monograph ‘Primary plastic surgery with rejected skin flaps’.